The Immunomodulatory Role of Calf Thymus Extract on Humoral and Cell Mediated Immune Response in Chicken Vaccinated Against New Castle Disease Virus - Naik, B.M. Chandra; Babu, Y. Hari; Mamatha, G.S. (International Journal of Poultry Science, 2005)
The effect of administration of calf thymus extract (CTE) with protein concentration of 1.8mg/ml was studied using two groups of day old layer chicks. Both the groups were vaccinated with ‘F’ and ‘R2B’ strains of New Castle Disease Virus (NDV) vaccines on 7th day and 8th week respectively. One group was administered with 1.8mg of thymic proteins intraperitoneally, one week prior and one week after each vaccination. The other group remained as vaccinated control group. Humoral and cell mediated responses were evaluated 15 days after each vaccination. Intraperitoneal administration of calf thymus extract markedly and significantly increased the antibody titres against NDV, serum globulin level, and percentage of lymphocytes in the blood. In addition thymus extract resulted in definite and significant cellular immunopotentiation.